Marianismo and the changing role of Latinas in educational leadership - Salazar Montoya, LeAnne C.; Kew, Kristin (Frontiers in Education, 2023)
This article focuses on the testimonios of accomplished Latina school leaders, shedding light on their upbringing, familial responsibilities, generational poverty, and commitment to challenge the prevailing narrative and break through institutional barriers. We provide an overview of how they shaped and navigated their professional careers despite various barriers and how they blazed new trails for future generations. Cultural norms, familial responsibilities, and uncommon mentorship models for Latina school leaders are discussed. These leaders often missed family gatherings and children's events but had found ways to balance work and life and care for their loved ones. They acted as role models of professional success for their family, friends, and colleagues. They were windows, mirrors, and sliding glass doors for those needing their support. Recommendations The women in our research serve as mentors (referred to as femtors) to other women in their fields. Through their achievements, they challenge and overcome the glass ceilings imposed by hegemonic systemic structures that favor and maintain existing social hierarchies by breaking through them. These structures often contribute to the marginalization of certain groups. Our findings from these testimonios fully capture the authenticity and essence of the participants' lived experiences while utilizing a feminist framework to construct research. The themes that emerged include (1) fostering a professional community linking one to other educational professionals, (2) participating in structured mentorship development programs throughout your career, (3) remaining a lifelong learner, (4) fostering professional relationships, and (5) remaining confident yet humble, and being one's authentic self. Finally, as the former Chancellor of New York Schools, Richard Carranza, often says, “Do not get lost trying to keep your job that you forget to do your job.” Our research delves into how these factors have led to their professional success and positioned them at the forefront of their fields. The pathways of the women in this study were similar in that their decisions led to positions of authority, namely superintendency, and gaining recognition for breaking through the traditional glass ceiling. We must consider whether generations of Latinas did not pursue careers or leadership positions outside their homes due to what they felt were their cultural and family obligations. Many agree that marianismo has prevented Latinas from reaching their goals.